Extension actions for men's health: an experience report (Research, Society and Development, 2020)
Objective: to report the experience lived by scholarship holders about the actions developed with young men and adults about their health, in the perspective of the promotion and prevention of diseases. Method: experience report from the beginning of the project, in March 2017 to September 2020, about the relationship of the male population with the preservation of their health, through the project “Taking care of men's health from the perspective of health promotion and prevention of grievances”, held at a public university in the city of Rio de Janeiro. Results: brings reflection and discussion with young men and adults about their relationship with health preservation and disease prevention, clarifying these issues through guidance on male gender issues, from the perspective of health promotion. Likewise, access to the health unit and the importance of adopting safe practices for their health are discussed. Final Considerations: the extension project encourages young men and adults to reflect on their health, bringing public health policies for men as drivers of action in health promotion and disease prevention, in the establishment of actions that fill gaps in knowledge and Research.